Right lobe liver transplantation in patient with fulminant form of the Wilson’s disease from AB0-incompatible relative donor - A. R. Monakhov; O. M. Tsiroulnikova; T. A. Dzhanbekov; D. Dzhiner; I. E. Pashkova; N. P. Mozheiko; K. M. Khizroev; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Wilson’s disease is a rare congenital disease caused by deficiency of the copper-transporting P-type ATPase-B enzyme. The course of disease varies widely from the latent form to the acute liver failure which is observed in 5% of Wilson’s disease cases. This clinical case represents experience of liver transplantation as the only curative treatment for patients with fulminant form of Wilson’s disease demonstrating excellent postoperative results. Living donor liver transplantation allows performing the operation in the shortest possible time which is necessary in acute liver failure. The plasmapheresis with plasma exchange AB (IV) allows preparing the patient for transplantation with incompatible blood group.